EFFECT OF ROCK SUBSIDENCE GENERATED BY EXTRACTION OF FLUIDS FROM PRODUCTIVE STRATA, ON MINE SHAFTS OR OIL AND GAS WELLS - Cherskiy N.V.; Tupysev M.K.; Vinogradov V.N.; Zhidenko G.G.; Savchenko V.V. (My University, 1988)
Rock subsidence as a result of the working of deposits of gaseous, liquid and solid minerals has the following consequences: (1) the lining of any vertical underground structure used in the mining industry will unavoidably be subjected to considerable axial loads; (2) the axial loads so created are in the tens or hundreds of megapascals; (3) the axial loads that have been identified are the main cause of deformation of the linings (casings) of vertical wells or shafts; (4) lining (casing) deformation can be eliminated by creating linings that are not rigidly fastened at the shaft head or bottom. We have derived equations for determining the normal stress in a casing string as a result of deformation of the pay stratum by extraction of fluids.